Factors related to the incidence of stunting in Nupabomba and Guntarano Villages, Tanantovea District, Donggala Regency. Issue 1 (April 2021) - Hasanudin; Djaafar, Tjitrowati; Saharudin; Bungawati, Andi
Abstract: People with stunting are generally susceptible to disease, have a level of intelligence below normal and have low productivity. The research objective was to determine the factors associated with stunting in children under. This study was an analytic study with a case control approach, the population in this study of all stunting cases in the villages of Nupabomba and Guntarano, Tanantovea District, Donggala Regency as many as 49 toddlers, the sample in this study was divided into two categories, namely the case group and the control group with comparisons. 1: 1. The bivariate test results showed that there was a relationship between the provision of clean water, toilet ownership and the habit of washing hands with soap in Nupabomba and Guntarano Villages, Tanantovea District, Donggala Regency. The factor of clean water supply, latrine ownership and the habit of washing hands with soap have a significant relationship with the incidence of stunting because the p value obtained is less than 0.05. It is hoped that Wani Puskesmas officers and cadres can provide education about the provision of clean water, ownership of a toilet that meets the requirements and the habit of washing hands with soap and can provide additional information about the relationship between sanitation facilities and stunting.